Synthesis and Pharmacological Evaluation of a Novel Peptide Based on Anemonia sulcata BDS-I Toxin as a New KV3.4 Inhibitor Exerting a Neuroprotective Effect Against Amyloid-β Peptide - Ciccone, Roselia; Piccialli, Ilaria; Grieco, Paolo; Merlino, Francesco; Annunziato, Lucio; Pannaccione, Anna (Frontiers in Chemistry, 2019)
There is increasing evidence that the fast-inactivating potassium current IA, encoded by Kv3.4 channels, plays an important role in Alzheimer’s Disease (AD), since the neurotoxic β-amyloid peptide1-42 (Aβ1-42) increases the IA current triggering apoptotic processes. The specific inhibition of Kv3.4 by the marine toxin extracted from Anemonia Sulcata, named blood depressing substance-I (BDS-I), reverts the Aβ peptide-induced cell death. The aim of the present study was to identify the smallest fragments of BDS-I, obtained by peptide synthesis, able to inhibit KV3.4 currents. For this purpose, whole-cell patch clamp technique was used to evaluate the effects of BDS-I fragments on Kv3.4 currents in CHO cells heterologously expressing Kv3.4. We found that BDS-I[1-8] fragment, containing the N-terminal octapeptide sequence of full length BDS-I, was able to inhibit Kv3.4 currents in a concentration dependent manner, whereas the scrambled sequence of BDS-I[1-8] and all the other fragments obtained from BDS-I full length were ineffective. As we demonstrated in a previous study, BDS-I full length is able to counteract Aβ1-42-induced enhancement of Kv3.4 activity, preventing Aβ1-42-induced caspase-3 activation and the abnormal nuclear morphology in NGF-differentiated PC-12 cells. Similarly to BDS-I, we found that BDS-I[1-8] blocking Kv3.4 currents prevented Aβ1-42-induced caspase-3 activation and apoptotic processes. Collectively, these results suggest that BDS-I[1-8] could represent a lead compound to be developed as a new drug targeting Kv3.4 channels.